Analisis Efektivitas Filtrasi Sederhana terhadap Kualitas Fisik-Kimia Air Sumur Bor dan Sungai Kahayan untuk Mitigasi Dampak Lingkungan - Yunida Iashania; Reni Agustiani; Asri Fridtriyanda; Valentinus Waruwu; Yunita Enzelina Silaban (Jurnal Fisika Unand, 2026)
The purpose of this study was to determine the effectiveness of the filter before and after filtration so that the water complies with water quality standards. The research method used a quantitative method with a field and laboratory experimental approach to test changes in air quality after going through a filtration process using a simple system designed. Based on research obtained from the laboratory, there was an increase in the effectiveness of well water quality of 95.65%, dissolved manganese (mn) of 83.87%, the color looked clearer with an increase of 68.47%, dissolved iron (Fe) of 14.63%, air acidity (pH) of 7.16%, nitrite (NO2) of 1.43%. While for river water the TSS value was 40.82%, dissolved oxygen (DO) of 121.03%, chemical oxygen demand (COD) of 14.16%, biological oxygen demand (BOD) of 12.82% and an increase in pH of 4.17%. The filter designed in this study is effective for use in water wells because it is able to filter and improve the quality of groundwater because it complies with water quality standards, namely PP No. 22 of 2021, while for river water it is still less effective in addressing air quality, especially in TSS and BOD values.